Readmissions After Guillain–Barre Syndrome: Nationally Representative Data. Issue 4 (June 2021) - Roberts, Mallory; Jin, Peter; Shin, Susan; Dhamoon, Mandip
Abstract : Objectives: We aimed to obtain nationally representative data on hospital readmission rates after Guillain–Barre syndrome (GBS). Methods: International Classification of Disease, Ninth Revision codes from the 2013 National Readmissions Database identified adult GBS admissions, comorbidities, and readmission diagnoses. Logistic regression estimated odds ratios (ORs) for readmission. Results: Of 2109 GBS admissions identified, 20.8% were readmitted within 1 year and 12.2% within 30 days. Age did not predict readmission. Plasmapheresis use showed a nonsignificant trend toward readmission versus intravenous immunoglobulin use [OR 1.43, 95% confidence interval (CI) 1.00–2.051, P = 0.050]. Respiratory failure (OR 1.70, 95% CI 1.23–2.35, P = 0.0014), heart failure (OR 2.14, 95% CI 1.25–3.66, P = 0.0057), and renal failure (OR 2.00, 95% CI 1.20–3.32, P = 0.0078) predicted readmission. Top readmission diagnoses included GBS or chronic inflammatory demyelinating polyneuropathy (42.0%) and sepsis (3.5%). Conclusions: One-fifth of GBS patients were readmitted within 1 year. Comorbid illnesses and respiratory complications increased a readmission risk but age did not.